Cyprus-Egypt Geopolitical Cooperation in Energy and Regional Security in the Eastern Mediterranean - Yusuf Idrus Malik; Askhari, Fitriah Islamiah (Middle Eastern Culture & Religion Issues, 2025)
This article examines the geopolitical dynamics of Cyprus-Egypt relations in the context of energy and security cooperation in the Eastern Mediterranean. The central issue addressed is how this bilateral partnership has evolved and what strategic interests underpin it. This research is guided by the question: how do Cyprus and Egypt construct and pursue their geopolitical interests through energy and security collaboration, and what are the broader implications for a regional constellation in the Eastern Mediterranean? Using a qualitative approach informed by Geopolitics Theory, Regional Security Complex Theory (RSCT), and Balance of Threat Theory, the study reveals that the Cyprus-Egypt cooperation is beyond natural resource exploration. Instead, represents a regional alliance aimed at counterbalancing Turkish influence. The author argues that this partnership signals a transformation in Middle Eastern geopolitical boundaries of the Middle East. The article concludes that Cyprus-Egypt relations exemplify a new geopolitical synergy that contributes to the emerging architecture of regional energy and security while prompting a redefinition of the Middle East’s cultural and political scope.